2018
DOI: 10.1002/hon.2523
|View full text |Cite
|
Sign up to set email alerts
|

Pathway‐focused gene expression profiles and immunohistochemistry detection identify contrasting association of caspase 3 (CASP3) expression with prognosis in pediatric classical Hodgkin lymphoma

Abstract: The search for clinically relevant molecular markers in classical Hodgkin lymphoma (cHL) is hampered by the histopathological complexity of the disease, resulting from the admixture of a small number of neoplastic Hodgkin and Reed-Sternberg (H-RS) cells with an abundant and heterogeneous microenvironment. In this study, we evaluated gene expression profiles of 11 selected genes previously proposed as a molecular score for adult cHL, aiming to validate its application in the pediatric setting. Assays were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 45 , 46 TGF‐β has been detected predominantly in nodular sclerosis (NS) HL and has potent anti‐inflammatory properties. 35 , 47 Caspase3 (CASP3) is a marker of cell death by apoptosis, and the fact that high levels of CASP3 + H‐RS cells correlate with a better outcome in adult 48 and pediatric 49 , 50 HL underscores its role in apoptosis of H‐RS cells. Thus, CASP3 can serve as a potential biomarker for response prediction of HL.…”
Section: Tme Modulatorsmentioning
confidence: 99%
“… 45 , 46 TGF‐β has been detected predominantly in nodular sclerosis (NS) HL and has potent anti‐inflammatory properties. 35 , 47 Caspase3 (CASP3) is a marker of cell death by apoptosis, and the fact that high levels of CASP3 + H‐RS cells correlate with a better outcome in adult 48 and pediatric 49 , 50 HL underscores its role in apoptosis of H‐RS cells. Thus, CASP3 can serve as a potential biomarker for response prediction of HL.…”
Section: Tme Modulatorsmentioning
confidence: 99%
“…We examined the spatial expression of marker genes previously reported for common cell types in two samples to assess the sensitivity of the method of detecting the transcripts per spot, and the results confirmed that ALB and CYP2E1 14 were highly expressed in para-carcinoma regions; GPC3 26 and AKR1B10 27 in carcinoma regions; ACTA2 and COL1A1 (markers typically associated with activated fibroblasts or cancer-associated fibroblasts) 28 in the fiber cord and stromal regions, and the above also confirmed the reliability of ST sequencing results. We also detected the spatial distribution of PTPRC (leukocyte marker) 29 , CD2 (T cell and NK cell marker) 30 , and LYZ (myeloid cell marker) 31 in two samples (Figure 1 E); however, no evident spatial characteristics of these markers were found.…”
Section: Resultsmentioning
confidence: 93%